Peningkatan Kapasitas Anggota KUD Anjasmoro Wonosalam dalam Pemasaran Produk Olahan Susu Sapi - Purmiyati, Atik; Sylviana, Widya; Jayadi, Akhmad (Universitas Muhammadiyah Malang, 2025)
Purpose –The purpose of this activity is to provide direct training to KUD administrators and their members for the sustainability of community service activities. In addition, empowering local communities through active involvement in product promotion is expected to strengthen marketing networks and increase the sense of ownership of local products. Design/methodology/approach – This community service activity is carried out using an active participatory method which consists of several stages. Starting from activity planning, preparation, implementation and evaluation. The stages of implementing the training are important because they provide a knowledge base of the AISAS marketing method to the administrators and members of KUD Anjasmoro. Findings - From the results of e-commerce training using AISAS techniques and WhatsApp Business Media, it can be seen that the training had an impact on increasing the capacity of Anjasmoro KUD members. In addition, wider use of technology and adoption of new digital platforms will strengthen KUD Anjasmoro's presence in the market, while strategic partnerships with various parties will support sustainable capacity increase. Originality – By implementing these strategies, KUD Anjasmoro can ensure that the e-commerce training that has been implemented not only has a positive impact in the short term, but also contributes to long-term, inclusive economic growth for all cooperative members and the surrounding community.